Trade and Industrial Dynamics in the Heyday of the Abbasid Dynasty: Historical Relevance to Contemporary Indonesian Economic Development - Resty Paryanda; Restu Asa Marisza Sukma; Arifah Rohmatul Hidayah; M. Arif Faizin (Eshraq: Journal of Islamic Studies, 2026)
This research discusses the dynamics of trade and industry during the heyday of the Abbasid Dynasty (750–1258 AD) and its relevance to contemporary Indonesian economic development. The Abbasid period is known as the golden phase of Islamic civilization which was characterized by the advancement of science, technology, and an integrated economic system. The Abbasid economy grew rapidly thanks to a combination of agricultural, manufacturing, and financial services sectors supported by strong institutions such as baitul mal and hisbah, as well as an efficient cross-regional trade system. Through a comparative historical approach, the study found that the success of the Abbasid economy rested on market integration, production specialization, and inclusive institutional governance. In the Indonesian context, the results of this study show that the national industrial and trade sectors still face the challenges of low added value, dependence on imported raw materials, and weak synergy between sectors. The Abbasid learning emphasizes the importance of strengthening economic institutions, developing logistics infrastructure, technological innovation, and improving the quality of human resources. By adapting the principles of efficiency, morality, and equity applied during the Abbasid period, Indonesia can strengthen the foundation of a competitive, inclusive, and sustainable industrial and trade economy in the era of globalization.